Böhmische Juden auf Wanderschaft über Prag nach Wien Charlotte von Weisls Familiengeschichte - Goltschnigg, Dietmar (2019)
The volume presents a Jewish family history written by Charlotte Weisl in 1931/32, dating back to the 17th century. The journey begins in small Bohemian rural communities and district towns and finally leads via Prague to Vienna, where the meeting with Zionism personified by Theodor Herzl begins a new phase. The First World War and the already emerging entry into the "age of Hitler" are the further drastic political events.